Elisha, man of grace - Westwood, Tom (Thomas Campbell) 1899- (Glendale, CA : The Bible Treasury Hour)
Elisha is undoubtedly one of the most picturesque types of our Lord to be found in the pages of the Old Testament. As a servant of God, he is characteristically "life-giving" as evidenced in the raising of the Shunammite's son, and the restoration of life to the dead body cast into his sepulchre. May his excellent steps of faith and power be an inspiration to the reader. - T.P.
Keywords: Elisha -- biblical prophet; Palestine, ancient -- religion -- biographies